2018
DOI: 10.1111/1462-2920.14465
|View full text |Cite
|
Sign up to set email alerts
|

The alternative sigma factor SigF is a key player in the control of secretion mechanisms in Synechocystis sp. PCC 6803

Abstract: Summary Cyanobacterial alternative sigma factors are crucial players in environmental adaptation processes, which may involve bacterial responses related to maintenance of cell envelope and control of secretion pathways. Here, we show that the Group 3 alternative sigma factor F (SigF) plays a pleiotropic role in Synechocystis sp. PCC 6803 physiology, with a major impact on growth and secretion mechanisms, such as the production of extracellular polysaccharides, vesiculation and protein secretion. Although Δsig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 65 publications
2
44
1
Order By: Relevance
“…Among the available techniques for quantitative proteomics, we chose iTRAQ in this study, as it is a well-established chemical labeling method in quantitative proteomics (Evans et al, 2012;Couto et al, 2014;Helliwell et al, 2017;Shi et al, 2017;Flores et al, 2019). As schematically reported in Figure 1, Control, +ASTM and +Infochemicals algal cultures were harvested after five days of growth plus either +2 h (n = 2) or +20 h (n = 2) of exposure, and then pelleted them by centrifugation at 3000 × g for 15 min at 4 • C. Cultures exposed to infochemicals exhibited flocculation, therefore we separated the supernatant (planktonic) fraction from the floc fraction.…”
Section: Protein Preparation and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the available techniques for quantitative proteomics, we chose iTRAQ in this study, as it is a well-established chemical labeling method in quantitative proteomics (Evans et al, 2012;Couto et al, 2014;Helliwell et al, 2017;Shi et al, 2017;Flores et al, 2019). As schematically reported in Figure 1, Control, +ASTM and +Infochemicals algal cultures were harvested after five days of growth plus either +2 h (n = 2) or +20 h (n = 2) of exposure, and then pelleted them by centrifugation at 3000 × g for 15 min at 4 • C. Cultures exposed to infochemicals exhibited flocculation, therefore we separated the supernatant (planktonic) fraction from the floc fraction.…”
Section: Protein Preparation and Quantificationmentioning
confidence: 99%
“…Unbroken cells and cell debris were pelleted by centrifugation at 18000 × g for 5 min and the supernatants transferred to clean Lo-Bind tubes. We estimated the total protein concentration by the modified Lowry method (Flores et al, 2019).…”
Section: Protein Preparation and Quantificationmentioning
confidence: 99%
“…Synechocystis SigF is known to directly regulate the transcription of the pilA1-pilA2 operon [ 122 ]. Deletion of sigF in Synechocystis correspondingly leads to a reduction in pilA1-pilA2 mRNA and a loss of thick pili and phototactic motility [ 123 , 124 ]. Furthermore, Flores et al found that sigF deletion significantly alters the exoproteome, with many proteins being present in reduced quantities or not at all [ 124 ].…”
Section: Regulation Of the T4p Machinerymentioning
confidence: 99%
“…Deletion of sigF in Synechocystis correspondingly leads to a reduction in pilA1-pilA2 mRNA and a loss of thick pili and phototactic motility [ 123 , 124 ]. Furthermore, Flores et al found that sigF deletion significantly alters the exoproteome, with many proteins being present in reduced quantities or not at all [ 124 ]. Although this may indicate a connection between T4P action and protein secretion, as has been found in S. elongatus PCC 7942, Flores et al also point out the large number of proteins of unknown function regulated by SigF, so definite conclusions on protein export will require further characterisation [ 124 ].…”
Section: Regulation Of the T4p Machinerymentioning
confidence: 99%
“…Mass spectrometry-based quantitative proteomics is considered an excellent strategy to investigate metabolism in biological systems by quantifying protein abundance (Parker et al, 2014;Russo et al, 2016;Flores et al, 2019;Raut et al, 2019). To evaluate the potential for using in vitro laboratory models of human skin as viable alternatives to animal testing, a mass spectrometry-based approach using both label-free quantitative proteomics and matrix-assisted laser desorption ionization (MALDI) imaging (Russo et al, 2018) was undertaken in this study.…”
Section: Introductionmentioning
confidence: 99%